Early pathology in sleep studies of patients with familial Creutzfeldt–Jakob disease. (2nd June 2016) - Givaty, Gili; Maggio, Nicola; Cohen, Oren S.; Blatt, Ilan; Chapman, Joab
Summary: In this study, we aimed to assess sleep function in patients with recent‐onset familial Creutzfeldt–Jakob disease (fCJD). The largest cluster of fCJD patients is found in Jews of Libyan origin, linked to the prion protein gene ( PRNP ) E200K mutation. The high index of suspicion in these patients often leads to early diagnosis, with complaints of insomnia being a very common presenting symptom of the disease. The study included 10 fCJD patients diagnosed by clinical manifestations, magnetic resonance imaging (MRI) scan of the brain, elevated tau protein in the cerebrospinal fluid (CSF) and positive PRNP E200K mutation. Standard polysomnography was performed after a brief interview confirming the presence of sleep disturbances. All patients showed a pathological sleep pattern according to all scoring evaluation settings. The sleep stages were characterized by (i) disappearance of sleep spindles; (ii) outbursts of periodic sharp waves and shallowing of sleep consisting in increased Stage 2 and wake periods during the night, as well as decrease of slow‐wave sleep and rapid eye movement (REM) sleep. Recordings of respiratory functions reported irregular breathing with central and obstructive apnea and hypopnea. The typical hypotonia occurring during the night and atonia during REM sleep were replaced by hyperactive sleep consisting of multiple jerks, movements and parasomnia (mainly talking) throughout the night. In conclusion, we report unique pathological sleep patterns in early fCJD associated with the E200K mutation. Specific respiratory disturbances and lack of atonia could possibly serve as new, early diagnostic tools in the disease.